Consumer Perception of Salted Fish Product in Bengkulu City - Yety Meyzella; Basuki Sigit Priyono; Ketut Sukiyono (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
The fulfillment of carbohydrate needs encourages people to gravitate toward higher-value menu items, such as animal protein. The ever-increasing human demand for animal protein is related to the human need for nutrition. To know and understand what consumers need and want, business actors must keep an eye on market developments, which can change at any time in response to shifting consumer needs. Therefore, business actors need to study carefully about consumers. This research aims to examine consumer perceptions of salted fish products in Bengkulu City. The research location was determined purposively, and 30 consumers were selected using accidental sampling. Consumer perception of salted fish is analyzed based on product attributes, namely taste, price, aroma, packaging, and services, measured using a Likert Scale. The results showed that salted fish products consumers in Bengkulu City have a good perception of overall product attributes.